The use of millet seeds on poultry nutrition: A review - Kaseb, Yasser Ghanim Salih; Al-Flayyih, Raghad Naseer Waleed; Al-Tamee, Nawaf Gazi Abood (Journal of agricultural, environmental and veterinary sciences, 2022)
Plant of Millet is one of field crop that is belongs to the family of Poaceae. All types of millet seeds contain of 11-14% crude protein, 2.93-7.69% ether extract, 1.96-9.40% crude fiber, 1.62-11.95% ash and 60.14-72.20% soluble carbohydrates, In addition to that it contains 0.21-3.50% lysine, 0.16 -1.20% methionine, 0.03-3.30% calcium and 0.08-3% phosphorous, while it contained 2675-3281 kcal./kg metabolism energy. Millet seeds also contain some Anti-Nutritional Factors such as phytic acid of 2380-4220 mg/kg, tannin 8-14600 mg/kg and saponin 173 mg/kg. Millet seeds can be used successfully in poultry nutrition, in starter and growing diets of broilers, it can be substituted partially or completely for maize cereal or using these seeds for 55% of the broilers’ diet. As for laying hens, seeds of millet can be used partly or totally replaced, or by adding 40-69% of the totality diet. Also, 100% of millet seeds replaced yellow corn or added 50% of the ration of broiler breeder chickens. Japanese quail’ diets the researchers were able used seed millet to partly or completely replace the yellow corn in the grower and layer diets, or 44% from totally ration to grower and layer quail. The same is the case with the diet of duck, as it was completely replaced millet seeds as a substitute for maize without any side effects. This also applies to the grower guinea fowl’ diets, as seeds of millet were completely substituted for corn. Finally, it was possible to feed pigeons on a diet completely millet seeds without any significant differences with the control ration.